+0  
 
0
227
3
avatar

How to write these without parentheses? Ty :)

 Jun 8, 2019
 #1
avatar+111435 
+2

We are using the exponent law  that  says that  (a^m)^n  =  a^(m*n)

 

(-3a^2b)^3   =   (-3)^3 * (a^2)^3 * (b)^3   =  -27a^6b^3

 

(5 - 2x)^2  =  (5 - 2x) (5-2x)  =  25 - 10x -10x + 4x^2  =  4x^2 -20x + 25

 

(5p^2q^3)^4  =  (5)^4 * (p^2)^4 * (q^3)^4  =  625p^8q^12

 

(-2xy^3)^4  =  (-2)^4 * (x)^4 * (y^3)^4  =  16x^4y^12

 

cool cool cool

 Jun 8, 2019
 #2
avatar
0

Thank you so much! They would look like this then, right?

Guest Jun 8, 2019
 #3
avatar+111435 
+2

Correct  !!!

 

 

cool cool cool

CPhill  Jun 8, 2019

13 Online Users